ASPEK TRANSPARANSI DALAM KUALITAS PELAYANAN PADA PENYEDIAAN AKSESIBILITAS TROTOAR JALAN BAGI PENYANDANG DISABILITAS TUNANETRA DI KOTA BANDUNG - Nia Karniawati; Widiyana Apriati (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
The provision of accessibility of the street pavement in Bandung City for the blind person are still not in accordance with needs and conditions. The theory of service used proposed by Sinambela (2008). According to him, there are six indicator of public service quality, namely: transparancy, accountability, condition, participation, sameness of right and the equal of right and abigation. And focus in this research just on transparancy. The method used is a qualitative research method with descriptive analysis. The results showed that in the tranparancy on quality service to providing acces pavement for the blind person in Bandung City in term of the openness in communication that Bandung City Government done. And in term of the openness in sosialization program for the blind person.